Innovative Method for Fabrication of Microwavable Denture Flasks - Sunil Dhaded; Rajesh Prajapat; Neha Dhaded (Wolters Kluwer Medknow Publications, 2011)
Introduction: Microwavable denture flasks for polymerization of acrylic resin are commercially available. However they are expensive and smaller in size, large maxillofacial prosthesis cannot be fabricated in them. The objective of this report is to showcase a simple technique for the fabrication of microwavable denture flasks which is economical and larger in size.Clinical innovation: A method of making dental stone flask pattern and a latex rubber mold was used to produce microwavable denture flasks. These flasks are made from the fiberglass liquid resin that is strengthened by the addition of chopped fiberglass strands.Discussion: Microwavable denture flasks can be made that will be simple, economical and large enough to accommodate the maxillofacial prosthesis. These flasks are strong enough for compression molding and allow successful microwave polymerization of acrylic resin denture bases.